If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x+2)-10+4x=2x+1-3(x-1)
We move all terms to the left:
3(x+2)-10+4x-(2x+1-3(x-1))=0
We add all the numbers together, and all the variables
4x+3(x+2)-(2x+1-3(x-1))-10=0
We multiply parentheses
4x+3x-(2x+1-3(x-1))+6-10=0
We calculate terms in parentheses: -(2x+1-3(x-1)), so:We add all the numbers together, and all the variables
2x+1-3(x-1)
determiningTheFunctionDomain 2x-3(x-1)+1
We multiply parentheses
2x-3x+3+1
We add all the numbers together, and all the variables
-1x+4
Back to the equation:
-(-1x+4)
7x-(-1x+4)-4=0
We get rid of parentheses
7x+1x-4-4=0
We add all the numbers together, and all the variables
8x-8=0
We move all terms containing x to the left, all other terms to the right
8x=8
x=8/8
x=1
| -8.7=x/4-2.3 | | 49x2=256 | | 1.6+x/3=-3.2 | | 1.6+x/3=3.2 | | x(x-4.5)=0 | | 1/2x+6=3x-4 | | 6p-7=5p+5 | | 5(x+2)=2-(2x+1) | | 8x-12x=42-18 | | x+(4x+6)+(6x-2)=180 | | 9×-3y=7 | | 4c−3=13 | | (x)=3/2(x-4)(x-4)+3 | | 5x+34=2x+76=90 | | 30+8y=14y | | -4(8x+29)=12 | | 6x+x+2x=720 | | 10p+9-11-p=-2(2p+4)-3(2p+4) | | 2x-1-2x-2=8 | | (2x+25)+(5x+2)=90 | | 7×y+1=-4-y | | 3x−15∘+5x−23∘=90∘ | | 5x+6+3x-8=180 | | 1/x+1/3x=1/18 | | F(x)=-2x^2+40x | | 93+76+(14x-7)+(11x-2)=360 | | 54x+7=75 | | 0.5x=0371+1 | | 8x+10=50* | | 0.8*(3x-2)-10.1=0.3*(x-4) | | C+1(8)=3c | | -7x-47=9 |